Undergraduate EFL students' Perception towards Online Learning and Its Impact on English Language Learning in Libya - Abdalaziz M. Toubot, (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2023)
The study examines the EFL students’ perceptions of online learning and its impact on English language learning. Also, it investigates the factors associated with using the Internet in improving students’ language skills. The sample of this study is 44 students who are studying English as a foreign language at the Faculty of Engineering, Bright Star University of Technology in Libya. The study utilized a quantitative approach to achieve the objectives of the study. The findings reveal that students have a moderate level (with a mean of 3.3739) of perception towards online learning and its impact on learning the English language. Besides, the study found there are no statistically significant differences in the perceptions of the students towards the Internet and its impact on English language learning related to students’ gender, whereas there are statistically significant differences in the perceptions of the students attributed to students’ experience in computer and Internet and how often they use the Internet weekly. The study recommends applying e-learning to enhance learning English language.